2014
DOI: 10.1097/ede.0000000000000046
|View full text |Cite
|
Sign up to set email alerts
|

In Utero Exposure to Compounds with Dioxin-like Activity and Birth Outcomes

Abstract: Results from this international general population study suggest an association between low-level prenatal dioxin-like activity and shorter gestational age, particularly in boys, with weaker associations for birth weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 62 publications
2
9
1
5
Order By: Relevance
“…The birth outcome most frequently investigated was birth weight (see Annex A.8.3, Table 67 therein). Some studies showed significant negative associations between maternal PCDD/Fs and DL‐PCBs exposure and birth weight (Vartiainen et al., ; Tajimi et al., ; Tsukimori et al., ; Konishi et al., ; Papadopoulou et al., , ), whereas others did not observe any statistically significant associations (Eskenazi et al., ; Halldorsson et al., ; Vafeiadi et al., ; Wesselink et al., ; Govarts et al., ). The strengths and the consistency of the associations varied and in general the studies have some major weaknesses such as exposure measured up to 40 years after the birth (Tsukimori et al., ) and doubts regarding confounders exemplified by a study where smoking was not associated with birth weight (Konishi et al., ).…”
Section: Assessmentmentioning
confidence: 99%
“…The birth outcome most frequently investigated was birth weight (see Annex A.8.3, Table 67 therein). Some studies showed significant negative associations between maternal PCDD/Fs and DL‐PCBs exposure and birth weight (Vartiainen et al., ; Tajimi et al., ; Tsukimori et al., ; Konishi et al., ; Papadopoulou et al., , ), whereas others did not observe any statistically significant associations (Eskenazi et al., ; Halldorsson et al., ; Vafeiadi et al., ; Wesselink et al., ; Govarts et al., ). The strengths and the consistency of the associations varied and in general the studies have some major weaknesses such as exposure measured up to 40 years after the birth (Tsukimori et al., ) and doubts regarding confounders exemplified by a study where smoking was not associated with birth weight (Konishi et al., ).…”
Section: Assessmentmentioning
confidence: 99%
“…Research based on representative sampling of the population at large [37] has documented that virtually every pregnant woman in the USA has at least 43 different environmental chemicals in her body. Persistent organic pollutants are found in pregnant and lactating women across the globe [25,38,39]. A report by the US National Cancer Institute found that “to a disturbing extent babies are born ‘pre‐polluted’” [40].…”
Section: Nature and Extent Of Prenatal And Preconception Exposure To mentioning
confidence: 99%
“…Although our current analysis uniquely studied how maternal smoking, black carbon, and PFASs may interact to influence birth size, prior studies have focused on how mixtures of other pollutants may impact birth weight. One study of about 1000 European mother-infant pairs observed a stronger negative cross-sectional association between cord blood dioxin-like activity and birth weight among infants of women who smoked during pregnancy versus non-smokers, but the interaction was not significant [ 47 ]. Another study of over 1000 mother-infant pairs from Greenland, Poland, and Ukraine observed greater birth weight reductions for infants of smokers concomitantly prenatally exposed to PFOA and di(2-ethylhexyl) phthalate (DEHP) versus non-smokers exposed to these two chemicals [ 48 ].…”
Section: Discussionmentioning
confidence: 99%